Una musica inaccettabile: il confronto tra il sinfonismo di Mahler e il pensiero di Wittgenstein (Lebenswelt. Aesthetics and philosophy of experience., 2024)
The following article confronts two extremely different ideas of music, namely the more traditional ideal of music of the Austrian philosopher Ludwig Wittgenstein and the innovative path taken on by the bohemian composer Gustav Mahler in its Symphonies.The harsh criticism of Mahler’s work done by Wittgenstein in its writings is widely known, he considered Mahler’s music as an inauthentic and sad product of the cultural crisis of their time.Nonetheless, it’s important to show how both tried to give answer to the same questions with their own opposite methods and ideas.Through the analysis of Wittgenstein criticism first and Mahler’s musical language second, this article aims to reconstruct the ways they tried and the difficulties they met in their quest to inspire people at a time when every cultural value seems to be questioned, by showing the similarities and contrasts in their thoughts about the nature of the musical language and the role of the artist in its relationship with the audience.